2022
DOI: 10.1136/bmjopen-2021-060681
|View full text |Cite
|
Sign up to set email alerts
|

Healthcare workers’ compliance with COVID-19 preventive measures, and associated factors, in Ethiopia: A systematic review and meta-analysis

Abstract: ObjectiveCompliance with COVID-19 prevention measures limits infection occurrence and spread in healthcare settings. According to research conducted in Ethiopia, compliance with COVID-19 preventative strategies is inconsistent among healthcare providers. This systematic review and meta-analysis aimed to estimate the national pooled proportion of healthcare workers (HCWs) who adhere to COVID-19 preventive measures and associated factors with good compliance.DesignA systematic review and meta-analysis of all ide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 64 publications
(134 reference statements)
0
3
0
Order By: Relevance
“…Moreover, the conventional facilities might be overburdened with treating both confirmed and nonconfirmed cases, and the overcrowding at the health facilities might have created inconvenient working conditions to strictly implement the IPC measures. Such scenarios have been reported by many studies 8,48,51,52 . One might need to further decipher the performance psychology of workers working in different health‐care settings, as this might provide us with directions on contents and modalities of training, supervision, and overall IPC improvement.…”
Section: Discussionmentioning
confidence: 85%
“…Moreover, the conventional facilities might be overburdened with treating both confirmed and nonconfirmed cases, and the overcrowding at the health facilities might have created inconvenient working conditions to strictly implement the IPC measures. Such scenarios have been reported by many studies 8,48,51,52 . One might need to further decipher the performance psychology of workers working in different health‐care settings, as this might provide us with directions on contents and modalities of training, supervision, and overall IPC improvement.…”
Section: Discussionmentioning
confidence: 85%
“… 22 However, there were other studies that cited a low level of compliance. This is the case of 49.7% healthcare workers in Ethiopia 8 and 58.5% in Nigeria, 23 among 12.3% residents of Dirashe district, southern Ethiopia 24 and 11.2% patrons of community convenience shops in Ghana. 25 Similarly, it was reported that at the beginning of the COVID-19 pandemic, preventives measures were not respected in sub-Saharan Africa as well as in the Rwandan community.…”
Section: Discussionmentioning
confidence: 96%
“…This implies that inadequate knowledge of COVID-19 prevention measures among nurses working in public hospitals in Dhaka can lead to the risk of infection and the spread of the virus. A study conducted in Ethiopia highlighted that inadequate training and knowledge of COVID-19 among healthcare workers led to a higher risk of contracting the virus (Zenbaba et al 2022). This also indicates that intensive training on COVID-19 prevention measures and regular updates about the pandemic is essential to control the spread of the virus.…”
Section: Discussionmentioning
confidence: 99%